Deteksi Fraudulent Financial Reporting dengan Menggunakan Perspektif Teori Fraud Pentagon - Jullani; Mukhzarudfa; Yudi (Magister Ilmu Akuntansi Universitas Jambi, 2020)
The purpose of this research is to examine the effect of fraud pentagon theory in explaining of fraudulent financial on Indonesian companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2018. This study uses 10 (ten) independent variables to achieve this objective, namely: financial stability, external pressure, auditor opinion, audit committee, change in auditors, rationalization, changes in directors, independent board of commissioners, political connections and CEO duality. The dependen variable used is fraudulent financial reporting proxied by restatement of annual report. The study population uses companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2018 period. The result shows that the audit opinion variable have an influences fraudulent financial reporting, while the variables of financial stability, external pressure, audit committee, auditor turnover, rationalization, change of directors, independent commissioners, political connections and CEO duality do not have an effect on fraudulent financial reporting.